Prevalence of asthma and respiratory symptoms in 15–17 year-old Greek-Cypriots by proximity of their community of residence to power plants: Cyprus 2006–07 - Middleton, Nicos; Kolokotroni, Ourania; Lamnisos, Demetris; Yiallouros, Panayiotis K.; Koutrakis, Petros (My University, 2014)
Objectives: Numerous studies have reported adverse effects of traffic pollution on respiratory health. Exposure to power plants emissions has not been as comprehensively studied. The prevalence of asthma and respiratory symptoms was investigated among 15-17 year-olds in communities in the vicinity of power plants in Cyprus in relation to the rest of the island. Study design: Cross-sectional study. Methods: Based on responses of 5817 participants to the ISAAC questionnaire, study outcomes were: active asthma (i.e. report of asthma and current symptoms), inactive asthma and respiratory symptoms without a diagnosis. Associations in terms of the distance of the participants' community to any of the three power plants were investigated in logistic models before and after adjusting for known confounders. Results: At 7.4% (95% CI: 4.5, 11.3), the prevalence of active asthma in communities at 5km of power plants appeared elevated but reduced to national levels of 5% at longer distances. Adjusted odds ratio for active asthma was 1.83 (95% CI: 1.04, 3.24) in the 5km zone compared to 30km away. No clear pattern was observed for inactive asthma while the odds ratio of respiratory symptoms in the absence of diagnosis was 0.76 (95% CI: 0.58, 1.01) in the affected communities. Conclusions: Higher prevalence of active asthma was observed in the vicinity of power plants, with no evidence of a distance-response relationship. With less than 5% of this age-group residing in close proximity to power plants, this corresponds to a small fraction of active asthma attributable to power plant emissions.
Keywords: Air pollution; Asthma; ISAAC; Power plants; Respiratory symptoms